Validation of Prognostic Circulating Cell-Free RNA Biomarkers HPGD, PACS1, and TDP2 in Colorectal Cancer Through TaqMan qPCR and Correlation Analysis - Chau Ming Kan; Xiao Meng Pei; Simon Siu Man Ng; Wing Wa Leung; Yee Ni Wong; Hennie Yuk-Lin Cheng; William Chi Shing Cho; Hin Fung Tsang; Sze Chuen Cesar Wong (Current Issues in Molecular Biology)
Circulating cell-free RNAs (cfRNAs) have emerged as promising non-invasive biomarkers for colorectal cancer (CRC), offering insights into the disease’s prognosis. This study investigates the prognostic significance of the specific cfRNA biomarkers HPGD, PACS1, and TDP2 by employing the Taqman quantitative PCR (qPCR) to evaluate their expression levels in a cohort of 52 CRC patients. The methodology involved a robust statistical analysis to assess correlations between cfRNA levels and clinical parameters, including survival rates and recurrence incidences. Findings revealed a significant upregulation in the expression of HPGD and PACS1, while TDP2 displayed varying results, indicating a complex role in disease dynamics. Notably, lower expression levels of HPGD were associated with reduced survival, suggesting its potential as a negative prognostic indicator. Conversely, TDP2 levels correlated strongly with increased risks of recurrence, highlighting its clinical relevance in monitoring disease progression. Overall, this study elucidates the intricate interplay between these cfRNAs in the CRC prognosis. The results advocate for further exploratory studies to validate PACS1’s potential as a prognostic marker and reinforce the clinical significance of HPGD and TDP2 in the context of CRC management, positioning them as vital elements in the landscape of molecular oncology.